The Best of Enemies, Movie Edition : Race and Redemption in the New South - Davidson, Osha Gray (Book collections on Project MUSE., 2019)
"C. P. Ellis grew up in the poor white section of Durham, North Carolina, and as a young man joined the Ku Klux Klan. Ann Atwater, a single mother from the poor black part of town, quit her job as a household domestic to join the civil rights fight. During the 1960s, as the country struggled with the explosive issue of race, Ellis and Atwater met on opposite sides of the public school integration issue. Their encounters were charged with hatred and suspicion. In an amazing set of transformations, however, each of them came to see how the other had been exploited by the South's rigid power structure, and they forged a friendship that flourished against a backdrop of unrelenting bigotry."--Page 4 of cover.